Potensi Homestay sebagai Daya Tarik Wisata di Desa Tempirai, PALI - Putri, Vania Okky; Hariman, Hariman; Permatasari, Mustika; Setiawan, Mulkan; Morena, M. Rian Ahdian (Politeknik Pariwisata Medan, 2024)
This research aims to identify and analyze the potential of homestays in Tempirai Village - PALI, which can be claimed as a tourism product in the region. This research is qualitative with a descriptive approach, which describes the existing conditions, especially accommodation in the form of homestays, as well as through potential analysis carried out on the 2A (Attractions and Accommodation) tourism product components. Data was collected through observation, interviews and literature study. The research results show that Tempirai Village has products that are quite ready to be developed as a tourist attraction, one of which is a Homestay with hospitality and a tourism-awareness by the local community. This potential is ultimately considered capable of supporting the development of Tempirai Village to become a tourist village in the future.